A model for sorption hysteresis in hardened cement paste. (September 2019) - Schiller, P.; Wahab, M.; Bier, T.; Mögel, H.-J.
Abstract: In hardened cement paste (C-S-H gel), water intercalated between the C-S-H layers can be adsorbed and desorbed by varying relative humidity. Sorption in the interlayer space between the C-S-H sheets is supposed to be responsible for low pressure hysteresis of water sorption isotherms. Additionally, large hysteresis loops also appear in diagrams that depict the humidity-dependent volume change of the paste. In contrast to most other porous solids, the volume of the C-S-H gel is larger along the desorption branch (drying) than along the adsorption branch (rewetting). Based on a macroscopic approach, we use a simple model to describe hysteresis in sorption and volume change diagrams. Computed hysteresis loops, which depend on the lateral extension of the interlayer spaces, are similar to loops observed experimentally.